Understanding the artistry of actors who create theatre with and for children. Issue 4 (1st October 2020) - Andersen, Jennifer
ABSTRACT: Actors create theatre with and for with children in diverse theatrical, educational and therapeutic contexts but little is known about the 'artistry' of their practice. This paper analyses a theatrical encounter between a child and an actor and identifies four key qualities of 'pedagogically tactful' (van Manen 2016) actor practice: listening, reciprocating, imagining and empathising. In doing so, the artistry of actors who work with children is interpreted as 'aesthetic judgement', involving a relationship between theatrical craft, pedagogy and care.